The Profile of Ergonomic Studies Published in Persian Scientific Journals of Iran (2011-2022): A Scientometric Study - Tara Rouhani; Narmin Hassanzadeh-Rangi; Yahya Khosravi (بهداشت و ایمنی کار)
Introduction: Scientometrics is a research field that examines and analyzes scientific trends and patterns in various scientific journals. This study aims to analyze the content of research published between 2011 and 2022 in Persian scientific journals focusing on ergonomics, to identify trends and the scientific direction in the field. Material and Methods: This study collected all articles published from 2011 to 2022 in Persian journals, including “Occupational Health,” “Occupational Health and Safety,” “Occupational Health Engineering,” “Iranian Journal of Ergonomics,” “Occupational Medicine,” and “Occupational Hygiene and Health Promotion,” using a census method from the journals’ websites. 368 articles were categorized based on thematic codes developed by experts, and data were analyzed using Excel 2010. Results: The theme “Physiological Status and Occupational Factors” had the highest frequency (17.65%), while “Ergonomics in Small Workplaces and Services” had the lowest (0%). Approximately 55% of the published studies were centered around themes including “Physiological Status and Occupational Factors,” “Ergonomics Methodology, Methods and Techniques,” “Inspection, Monitoring, and Evaluation of Performance,” and “Characteristics of Physiology and Cognitive Processes.” The research focus in ergonomics tends to prioritize methodology and innovation over the practical application, emphasizing industrial needs over those in services and agriculture, and favoring large workplaces over small or construction sites. Conclusion: The thematic framework and publication patterns can serve as valuable sources of information for educational and research planning within the field of ergonomics for universities, research centers, and related organizations; it can contribute to the scientific advancement of the field and lead to its overall improvement.